A multicenter, open-label, uncontrolled, single-arm phase 2 study of tirabrutinib, an oral Bruton's tyrosine kinase inhibitor, in pemphigus. Issue 3 (September 2021) - Yamagami, Jun; Ujiie, Hideyuki; Aoyama, Yumi; Ishii, Norito; Tateishi, Chiharu; Ishiko, Akira; Ichijima, Tomoki; Hagihara, Shunsuke; Hashimoto, Koji; Amagai, Masayuki
Highlights: Tirabrutinib, an oral BTK inhibitor, was evaluated in patients with pemphigus. The complete remission rate with tirabrutinib after 24-week treatment was 18.8 %. The cumulative complete remission rate after 52-week treatment was 50.0 %. No relationship with tirabrutinib was observed for serious AEs and Grade ≥3 AEs. Tirabrutinib may be a new treatment option for patients with refractory pemphigus. Abstract: Background: The treatment of pemphigus is based on systemic corticosteroid use and adjuvant therapies, but some patients are resistant to conventional therapy. Tirabrutinib is a highly selective oral Bruton's tyrosine kinase inhibitor that may be clinically effective in treating pemphigus by suppressing B-cell signaling. Objective: We investigated the efficacy and safety of tirabrutinib in patients with refractory pemphigus. Methods: This was a multicenter, open-label, single-arm phase 2 study of Japanese patients with refractory pemphigus receiving appropriate treatment with an oral corticosteroid and adjuvant therapies. Patients received postprandial oral tirabrutinib 80 mg once daily for 52 weeks. After 16 weeks of tirabrutinib treatment, the corticosteroid dose was tapered to ≤10 mg/day of prednisolone equivalent. Results: In total, 16 patients were evaluated (mean age, 52.5 years; 50 % male). The complete remission rate after 24 weeks of treatment (primary endpoint) was 18.8 % (3/16; 95 % confidence interval, 6.6 %–43.0 %). By Week 52, eight patients (50.0 %) achieved complete remission and 10 patients (62.5 %) achieved remission. Over 52 weeks of treatment, the mean prednisolone dose decreased from 17.03 to 7.65 mg/day. Incidences of adverse events (AEs) and adverse drug reactions were 87.5 % and 43.8 %, respectively. A relationship with tirabrutinib was ruled out for all serious AEs and Grade ≥3 AEs. Conclusion: Treatment with tirabrutinib enabled remission and reduced oral corticosteroid exposure over time and did not result in any major safety concerns in patients with refractory pemphigus. Thus, oral tirabrutinib may be a new treatment option for patients with refractory pemphigus.